The Effect of Search, Solve, Create and Share (SSCS) Learning Model on Students’ Scientific Literacy - Rubiko Ihsan; Tonih Feronika; Evi Sapinatul Bahriah (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the effect of a Search, Solve, Create, and Share (SSCS) Learning models on students’ scientific literacy. The method used in this study was quasi experimental design, with research design nonequivalent control group. Population of this study were all the student’s of XI science classes. The sample was taken by purposive sampling and obtained 2 classes included XI science 1 and 2 as control and experimental class with the total number of each classes were 28 students. The data were collected through multiple choice test consisting of 20 items related to scientific literacy. The data obtained were analyze by independent sample t-test. The test result of independent sample t-test show sig (2-tailed) 0,05 at significance 5%, then H1 is accepted. The result indicated that Search, Solve, Create, and Share (SSCS) a significance effect on student’s scientific literacy on colloid system concepts.